Towards improving engagement of youth of color in cross-age mentoring programs in high poverty, high crime neighborhoods. (September 2021) - Wathen, Maria V.; Decker, Patrick L.F.; Richards, Maryse H.; Tyson McCrea, Katherine; Onyeka, Cynthia; Weishar, Charity N.; DiClemente, Cara; Donnelly, Will
Highlights: For all participants, traveling to a higher-crime program area was negatively related to attendance. Mentor variables related to attendance for mentors included stress, perceived family resources, and race. Variables related to attendance for mentees included age and having a sister in the home. Funding for programs in high-poverty, high-crime neighborhoods must budget for transportation. Abstract: This study examines predictors of attendance in a cross-age youth mentoring program offered in four high-poverty, high-crime communities. Youth in greatest need of after school and summer interventions are those residing in such communities, but programs are scarce. More specific to mentoring programs that do exist, past research has demonstrated the significance of attendance as a predictor of positive outcomes. Two datasets were combined for this study: The Saving Lives, Inspiring Youth (SLIY) mentoring program dataset and a neighborhood database. OLS regression results show that for all participants, traveling from a lower-crime home area to a program in a higher-crime area was negatively related to attendance, as was age. In addition to crime, variables related to attendance for mentors included stress, perceived family resources, and race, whereas age and having a sister were related to attendance for mentees. Implications for program designers and policymakers are discussed.